REVIEW OF CREW OBSTACLES IN THE PROCESS OF FULFILLING THE COMPLETENESS OF SPEEDBOAT MANNING CERTIFICATION OPERATING AT THE UPTD LLASDP KUALA TUNGKAL - Santoso, Santoso; Taufiqurrahman, Muhammad; Amrillah, Muhamad Fahmi; Utami, Fisca Dian; Maridyah, Rodhyatam (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2024)
West Tanjung Jabung Regency has river transportation, one of which is the UPTD LLASDP managed by the Tanjung Jabung Barat Regency Transportation Agency which operates almost 24 hours connecting villages, sub-districts and provinces in Kuala Tungkal. There are still many ship owners in UPTD LLASDP Kuala Tungkal who have not been certified, both for ship crews and ship operators who do not have awareness of shipping safety, which causes many problems in ship operations in terms of security, comfort and safety. The purpose of this study was to analyze the completeness of speedboat crew certification at the UPTD LLASDP Kuala Tungkal pier in accordance with applicable provisions and to analyze the obstacles experienced by Ship Crews in fulfilling Ship Certification at the UPTD LLASDP Kuala Tungkal pier. There are 100% of speedboats that do not have crew certificates. Some of the obstacles expressed by ship operators in fulfilling ship crew requirements are that 44% of ship operators do not have the funds to make ship crew certificates, where the requirement is that ship crews must have a Basic Safety Training (BST) certificate. As many as 28% of ship operators admitted that they did not understand the importance of using ship crew certificates and the obligation to have ship crew certificates.